2015
DOI: 10.5812/asjsm.6(2)2015.22838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eight-week Resistance Training Program in Men With Multiple Sclerosis

Abstract: Background:Muscle weakness and fatigue contribute to the reduction of daily activity in multiple sclerosis (MS) patients. Therapeutic strategies to promote improvements in muscle strength and endurance are limited in individuals with MS. Some evidence showed that exercise may improve and affect different aspects of the disease including quality of life, fatigue, motor and cognitive functions.Objectives:To investigate the value of resistance training of moderate to high intensity on motor function, muscle stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 25 publications
4
39
1
4
Order By: Relevance
“…Additionally, 6 weeks of isokinetic strength training are sufficient to increase maximum strength and reduce the levels of fatigue in the ankle dorsiflexors of MS patients [40], which showed that a very short circuit training program with elastic bands designed for MS patients generates modest improvements in power, an increase in functional capacity and a reduction of their perception of fatigue. Similarly, the same training period performed three times per week by means of seated rowing, chest press, leg extension and leg press exercises significantly improved performance in the 10 m timed walk test, the 3 min step test and the timed up and go test, with no significant effects on balance [41]. The discrepancies between the previous two studies and this one, concerning the effects of strength training on body balance, can be attributed on the one hand to the different instruments utilized for assessment, and on the other hand to the different type of contraction performed: in this research, the use of elastic bands instead of gym machines or calisthenics exercises can account for a continuous and greater stimulus of neuro-muscular coordination, which reflects positively on body balance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 6 weeks of isokinetic strength training are sufficient to increase maximum strength and reduce the levels of fatigue in the ankle dorsiflexors of MS patients [40], which showed that a very short circuit training program with elastic bands designed for MS patients generates modest improvements in power, an increase in functional capacity and a reduction of their perception of fatigue. Similarly, the same training period performed three times per week by means of seated rowing, chest press, leg extension and leg press exercises significantly improved performance in the 10 m timed walk test, the 3 min step test and the timed up and go test, with no significant effects on balance [41]. The discrepancies between the previous two studies and this one, concerning the effects of strength training on body balance, can be attributed on the one hand to the different instruments utilized for assessment, and on the other hand to the different type of contraction performed: in this research, the use of elastic bands instead of gym machines or calisthenics exercises can account for a continuous and greater stimulus of neuro-muscular coordination, which reflects positively on body balance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, group exercise training has a beneficial effect on improvement of the balance, quality of life, and preservation of functional status [20]. Resistance training program on patients with MS demonstrated that these exercises improved muscle strength, balance, seated rowing, and leg extension on the treatment group [12].…”
Section: Discussionmentioning
confidence: 99%
“…Isometric exercises are very simple and do not require any special tools. Thus, these exercises can be suggested for different age groups as patients can do them at any time of the day and in every situation [12]. To the best of our knowledge, there is no specific study conducted on the impacts of isometric exercises on MS patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following exercise rehabilitation/therapy pwMS experienced significant improvements in muscle characteristics. In particular, improvements in muscle strength, muscle endurance, muscle mass, neuromuscular function or neural drive were reported after (progressive) resistance [70][71][72][73][74][75][76][77][78][79][80][81] or combined (resistance and endurance) exercise training [82;83]. Improvements were even higher after high-intensity exercise training, suggesting that these changes are exercise intensity related [82][83][84].…”
Section: Muscle Function and Exercise In Msmentioning
confidence: 99%